2020
DOI: 10.3390/antibiotics9060345
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings and Antimicrobial Susceptibility of Anaerobic Bacteria Isolated in Bloodstream Infections

Abstract: The objectives of this study were to report on the antimicrobial susceptibility of 141 clinically significant anaerobic bacteria isolated from bloodstream infections between January 2016 and April 2020 in a tertiary-care hospital in Granada (Spain) and to describe the main clinical features of the patients. Species identification was performed by MALDI-TOF MS (Bruker Daltonics, Billerica, MA, USA). Antimicrobial susceptibility tests were performed against penicillin, amoxicillin-clavulanic acid, imipenem, moxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…In our study, susceptibility to moxifloxacin greatly varied depending on the species (9–43%), which is concordant with observations reported in the literature (0–48%) [ 20 , 23 , 25 , 26 , 30 , 31 , 32 , 37 ]. In agreement with these studies, we also observed that F. magna was more resistant than other species.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, susceptibility to moxifloxacin greatly varied depending on the species (9–43%), which is concordant with observations reported in the literature (0–48%) [ 20 , 23 , 25 , 26 , 30 , 31 , 32 , 37 ]. In agreement with these studies, we also observed that F. magna was more resistant than other species.…”
Section: Discussionsupporting
confidence: 93%
“…As observed here, clindamycin resistance rates among GPAC vary widely and this resistance is rising, especially in F. magna (3–51%) and Peptoniphilus spp. (1–36%) for which MIC 90 range from 2 to >256 mg/L [ 11 , 16 , 17 , 19 , 20 , 22 , 23 , 25 , 26 , 37 ]. In a recent global program (T.E.S.T.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood cultures accounted for almost 16% of all tested isolates. In this group, 22% were Gram-negative with the distribution of isolates comparable with previous reports [ 43 ]. Although it can be difficult to authenticate the relevance of the presence of bacteria that are part of the normal skin microbiota such as Cutibacterium , the presence of certain Gram-positive and most Gram-negative anaerobes in blood cultures almost always represents true bacteremia [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
“… 20 A different retrospective study revealed that 43.9% of anaerobic bacteria belong to the genus Bacteroides , 7% to the genus Fusobacterium , and 2.1% to the genus Prevotella . 21 Currently, studies on the analysis of anaerobic bacteria in postpartum infections with BSI are scarce, additional attention should be paid to BSI caused by anaerobes among postpartum women, and more efforts should be spent identifying the potential sources of anaerobe infections and guiding clinicians in rational drug use according to population characteristics in the future.…”
Section: Discussionmentioning
confidence: 99%